Exodus of the Hungarian minority from Ukraine? War-induced ethnic dynamics in the Ukrainian-Hungarian border region - Erőss Ágnes; Kovály Katalin; Коваль Катерина; Tátrai Patrik (Routledge, 2024)
Abstract. This chapter focuses on the Hungarian minority in Transcarpathia, Ukraine and intends to explore how (geo)political shifts since 2010 (the landslide victory of the right-wing populist Fidesz party in 2010 in Hungary, the Donbas conflict from 2014, and the full-scale Russian invasion in 2022) impacted this ethnic minority. Before February 2022, approximately 130,000 ethnic Hungarians resided in Transcarpathia, forming a relatively compact ethnic settlement along the Hungarian border. This well-organised community developed full-scale educational, cultural, and religious institutions, relying on their kin-state's support. Since the beginning of the armed conflict in Donbas, similarly to other Visegrad countries, Hungary was also active in draining the labour force from Transcarpathia. However, Hungary's kin-state politics (especially the implementation of non-residential citizenship in 2011) mainly influenced local Hungarians’ migration strategies. The analysis of quantitative and qualitative data confirmed that the outbreak of the full-scale war in Ukraine in 2022 induced dramatic changes: thousands of ethnic Hungarians have left Transcarpathia and typically resettled in Hungary as Hungarian citizens. Since this emigration is selective, the demographic and social composition of the Transcarpathian Hungarian population has already been distorted. Combined with the arrival of the IDPs, the ongoing processes impact the social and demographic position of the Hungarian minority in Transcarpathia.
https://www.taylorfrancis.com/books/edit/10.4324/9781003470601/minorities-war-elmira-muratova-nadia-zasanska?refId=8f6c26f4-77e7-4202-819e-c31459dfc66d&context=ubx
Keywords: Hungarian minority; Ukraine; migration; Transcarpathia